Output Persistence and Upside Down Electoral Business Cycles, What Does Really Matter? - Caleiro, António (2013)
This note shows in what circumstances output persistence may invert the pattern of the electoral cycle when inflation expectations are of the adaptive or rational type and the government preferences are quadratic over output and inflation